Analysis of the Financial Performance of PT Telkom Indonesia Tbk: Study of Profitability Ratio, Liquidity Ratio and Solvency for the Period 2022–2024 - Septian, Alvin Amirudin; Putri, Winda Maesya Tiana; Zahrani, Ardiana; Iory, Muhammad; Rakhman, Arif (Peneliti.net, 2025)
This report discusses the development and performance of PT Telkom Indonesia Tbk in the period 2022 to 2024. Telkom implements a Five Bold Moves strategy to strengthen its position as a leading digital telecommunications company in Indonesia. Key focuses include data center infrastructure expansion, network and digital service development, and improved operational efficiency through innovation and strategic collaboration. Financial performance in 2023 showed significant revenue and net profit growth, supported by successes in the data center, enterprise services, and telecommunications tower network sectors. In 2024, the company continues capacity building and digital innovation with various major projects including the construction of a Hyperscale Data Center and the implementation of InfraCo. Commitment to sustainability and ESG principles are also part of Telkom's long-term strategy. Overall, these innovations and investments support the company's vision to become a pioneer in Indonesia's digital transformation and improve national competitiveness.